Green tea - A short review - Rishi Raj Shrivastava, Rishi Raj Shrivastava; Pradeep Pateriya, Pradeep Pateriya; Mahendra Singh, Mahendra Singh (International Journal of Indigenous Herbs and Drugs, 2018)
Green tea, which is produced from the leaves of the Camellia sinensis plant and belongs to the family Theaceae, is one of the most popular beverages worldwide. Over the past 30 years or more, scientists have studied this plant in respect to potential health benefits. The health benefits of green tea for a wide variety of ailments, including different types of cancer, heart disease, and liver disease, were reported. Many of these beneficial effects of green tea are related to its catechin, particularly (-)-epigallocatechin-3-gallate, content. There is evidence from in vitro and animal studies on the underlying mechanisms of green tea catechins and their biological actions. There are also human studies on using green tea catechins to treat metabolic syndrome, such as obesity, type II diabetes, and cardiovascular risk factors. Long-term consumption of tea catechins could be beneficial against high-fat diet-induced obesity and type II diabetes and could reduce the risk of coronary disease. This review is done to spread awareness among general population about the benefits of green tea.